2022
DOI: 10.3389/fnut.2022.925908
|View full text |Cite|
|
Sign up to set email alerts
|

Citrate Synthase Insufficiency Leads to Specific Metabolic Adaptations in the Heart and Skeletal Muscles Upon Low-Carbohydrate Diet Feeding in Mice

Abstract: A decrease in TCA cycle activity may lead to impaired nutrition metabolism and cellular energy shortage. Herein, we aimed to characterize the detailed metabolic changes that compensate for energy shortages in energy-consuming organs (heart and skeletal muscles) in mice with knockout of citrate synthase (CS), an important enzyme in the TCA cycle. CS hetero knockout (CS +/−) mice and wild-type mice were fed a low-carbohydrate ketogenic diet (LCKD) or high-fat, high-carbohydrate diet (HFHCD) to induce metabolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
1
0
1
Order By: Relevance
“…Interestingly, metabolic alterations (including reduced levels of glycogen and increased expression of genes that promote mitochondrial OXPHOS) in the CS knock-down mouse model only occurred under fasting-mimic conditions [50]. The fact that our MT mice experienced fasting-mimic conditions (upregulated lipid cycling, downregulated lipogenesis and Glu4 expression) is consistent with the phenomena of mild insulin resistance [51].…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, metabolic alterations (including reduced levels of glycogen and increased expression of genes that promote mitochondrial OXPHOS) in the CS knock-down mouse model only occurred under fasting-mimic conditions [50]. The fact that our MT mice experienced fasting-mimic conditions (upregulated lipid cycling, downregulated lipogenesis and Glu4 expression) is consistent with the phenomena of mild insulin resistance [51].…”
Section: Discussionsupporting
confidence: 71%
“…Citrate synthase is the initial enzyme of the Krebs cycle and is important in the production of energy via mitochondrial respiration (i.e., oxidative phosphorylation) [ 121 ]. The enzyme is considered a biomarker for cellular oxidative capacity and mitochondrial content in striated muscle following a training regimen [ 37 , 122 , 123 ]. In this study, we observed an increased citrate synthase activity in LV tissue following MIT and HIIT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PD is associated with acetyl-CoA synthesis and TCA cycle dysfunction. When combined with respiratory chain dysfunction, this can exacerbate bioenergetic deficits [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%